CERPEN PEREMPUAN TANPA NAMA: MARGINALISASI DAN INFERIORITAS PEREMPUAN (TANTANGAN MENUJU SASTRA YANG MEMBEBASKAN) - Luh Putu Sendratari (Universitas Pendidikan Ganesha, 2017)
Literary works are often interpreted as a medium for the distribution of artistic desires alone. In fact, such a worldview is a mirror of superficiality in understanding literature. Kadek Sonia Priscayanti's short story is one of literary works critical of gender issues, especially in women's bodies, through what women's bodies are viewed and how the body is treated socially and culturally. Semiotic method used to dissect this work with interpretation supported by critical theory about Antonio Gramscie dominance / hegemony, Derrida decontruction and Bourdieu Interpretatif Kontrukstif hence can be found there is depiction of marginalization, inferioritas woman and way of woman do resistance to condition of injustice that happened. At least, this work adds to the list of articles that are sensitive to gender issues and can be an inspiration for the development of the Gender Mainstreaming program in the School World through the aspirations of literary works.Keywords: marginalization, inferiority, resistance, Gender Mainstreaming